2021
DOI: 10.3390/agriculture11030237
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Toxigenicity of Mycobiota in Grain Corn: A Case Study at Pioneer Grain Corn Plantations in Terengganu, Malaysia

Abstract: Malaysia has begun to locally mass-cultivate grain corn to reduce import dependency for animal feed industries. Since the Malaysian tropical climate constantly exposes grain corn to fungal colonization and mycotoxin production by mycotoxigenic species, it is, therefore, important to investigate the presence of fungal species, especially the mycotoxigenic strains in the Malaysian grain corn agroecosystem. In the present work, corn kernel, tassel, plant debris, and soil were collected from two pioneer grain corn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 82 publications
(96 reference statements)
2
7
0
Order By: Relevance
“…Interestingly, our investigation, on the contrary, revealed that location had no significant ( p > 0.05) effect on the toxigenicity of the fungal isolates. Our results on the effect of location on the fungal mycotoxin profiling agree with those of Yazid et al [ 44 ], who found that agro-ecological location has no influence on AFB 1 formation by A. flavus invading grain corn farms (Kampong Dadong and Rhu Tapai) in Terengganu, Malaysia. The authors emphasized that the mycotoxigenicity of the fungal isolates is more dependent on fungal strain specificity than geographical locations.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Interestingly, our investigation, on the contrary, revealed that location had no significant ( p > 0.05) effect on the toxigenicity of the fungal isolates. Our results on the effect of location on the fungal mycotoxin profiling agree with those of Yazid et al [ 44 ], who found that agro-ecological location has no influence on AFB 1 formation by A. flavus invading grain corn farms (Kampong Dadong and Rhu Tapai) in Terengganu, Malaysia. The authors emphasized that the mycotoxigenicity of the fungal isolates is more dependent on fungal strain specificity than geographical locations.…”
Section: Discussionsupporting
confidence: 91%
“…A. niger has been documented as one of the major OTA producers of agricultural products [ 44 , 45 ]. However, OTA production by Aspergillus spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To lessen the country’s dependency on importation, the Ministry of Agriculture and Food Industries has gazetted grain maize as one of the five new wealth-generating crop commodities alongside coconut, durian, dairy, and culinary industries (Bank Negara Malaysia 2018 ). This entails more land exploitation for the mass-cultivation of grain maize, following which, two pioneer grain maize plantations have been established in Kampong Dadong (13 hectares cultivated area) and Rhu Tapai (3.8 hectares cultivated area) in Terengganu, Malaysia (Yazid et al 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Among the primary challenges in developing and applying BCA is ensuring mycotoxin inhibition instead of mycotoxin stimulation which is common among mycotoxigenic fungal species in the face of habitat / nutrient competition with the applied BCA. In a previous work (Yazid et al 2021 ), we isolated and identified morphologically and molecularly several BCA candidates as well as characterising the mycotoxin potentials of several mycotoxigenic fungal species from two pioneer grain maize farms in Terengganu, Malaysia. In the present work, we therefore examined the antagonistic potential of those BCA candidates in vitro using the dual-culture assay on grain maize agar.…”
Section: Introductionmentioning
confidence: 99%